2017
DOI: 10.7440/res60.2017.02
|View full text |Cite
|
Sign up to set email alerts
|

Social Group Dynamics and Patterns of Latin American Integration Processes

Abstract: Dinámicas de grupos sociales y procesos de integración en América LatinaR E S U M E N | Este artículo propone incorporar elementos de la psicología social a las perspectivas tradicionales de la ciencia política y de las relaciones internacionales para explicar las dinámicas contradictorias de los procesos de la integración latinoamericana. Mediante un análisis teórico, responde al desafío planteado por Dabène (2009) para explicar la "resiliencia" de la agenda integracionista en la región a pesar de su "inestab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The present wave of scholarship continues to include characteristics of the first and second wave. For example, Dubé and Thiers () utilized the groupthink model to explain contradictory patterns related to integration processes in Latin America. Forsberg and Pursiainen () also utilize the groupthink dynamic as part of their explanation of Russia's annexation of the Crimean Peninsula in 2014.…”
Section: Key Models Of Group Decision‐making Dynamics In Foreign Policymentioning
confidence: 99%
See 1 more Smart Citation
“…The present wave of scholarship continues to include characteristics of the first and second wave. For example, Dubé and Thiers () utilized the groupthink model to explain contradictory patterns related to integration processes in Latin America. Forsberg and Pursiainen () also utilize the groupthink dynamic as part of their explanation of Russia's annexation of the Crimean Peninsula in 2014.…”
Section: Key Models Of Group Decision‐making Dynamics In Foreign Policymentioning
confidence: 99%
“…Janis's case studies relating to groupthink decision‐making dynamics related to Japan's attack on Pearl Harbor (1941), the escalation of the war in Korea (1950), Bay of Pigs operation (1961), and the involvement of the U.S. in the Vietnam conflict under President Johnson focus on the decision stage. More recent examples of groupthink during this stage include the 2003 decision of the Bush administration to invade Iraq (Mintz & Wayne, 2016a), the 2014 decision of the Obama administration to fight ISIS in Iraq and Syria (Mintz & Wayne, 2016a), the 2014 decision by Russia to annex the Crimean Peninsula (Forsberg & Pursiainen, ), and the policy decisions related to integration processes in Latin America (Dubé & Thiers, ).…”
Section: Policy Stages and The Dominant Group Dynamicmentioning
confidence: 99%
“…Studies have shown that psychological need thwarting decreases individuals’ stay intent ( Chen et al, 2020 ; Huyghebaert et al, 2018 ). Research on the black sheep effect points out that it is extremely stressful for a group member when they feel different from the group, which can relate to behavior or decision-making ( Dubé & Thiers, 2017 ). Members who deviate from a group norm (e.g., black people in a predominantly white society, or overly masculine females) may easily experience problems in a group, such as pressure and exclusion behavior from peers and inappropriate treatment from managers ( Breakwell et al, 2003 ; Cranmer & Cranmer, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…If states are human organizations, and regional organizations are, too, the repeated reproduction of similar organizations may be best explained as social group dynamics. A recent and indeed innovative theoretical approach is pioneered by Dubé and Thiers (2017). They consider Latin American and South American countries as a group and explain regional dynamics quite in a manner social psychologists would.…”
Section: Groups and Social Psychologymentioning
confidence: 99%
“…Nolte and Comini (2016) part from a similar ontology as Dubé and Thiers (2017) an insight into the importance given by Latin American leaders to presenting their countries as part of certain regional organizations at the United Nations General Assembly. Using interpretations borrowed from social psychology, Dubé and Thiers (2017) offer a plausible explanation as to why a seemingly unproductive regional integration dynamic keeps being reproduced in the same regional space.…”
Section: Groups and Social Psychologymentioning
confidence: 99%